Psychiatric advance directives and consent to electroconvulsive therapy (ECT) in Australia: A legislative review and suggestions for the future. (November 2022) - Wilson, Kay; Purushothaman, Subramanian; Kolur, Uday
Abstract: Psychiatric Advance Directives (PADs) have been adopted in many jurisdictions around the world and in most Australian states and territories. They are seen as a less restrictive and patient-centered approach to the provision of mental health care. Electroconvulsive therapy (ECT) is a restricted treatment in most jurisdictions in Australia and across the world. This paper explores the history, regulation and use of ECT and PADs and the intersections between them. It provides an overview of the legislative framework in each Australian state and territory and explores some of the issues which have arisen such as complexity of the regulatory framework, making PADs binding for refusing and consenting to ECT, involving treating teams in how PADs are made, using restrictive interventions to implement PADs, and the role of the Tribunal. While PADs are often framed as an important legal tool for allowing patients to refuse psychiatric treatment (especially ECT), the paper emphasizes that they can also be an innovative way for people to consent to psychiatric treatment in advance and an empowering option to access mental health care. It then makes some suggestions for future reform.